We have to solve the following set of simultaneous equations:

x + 3y = 2 ...(1)

2x + 8y = 6 ...(2)

2*(1) - (2)

=> 2x + 6y - 2x - 8y = 4 - 6

=> -2y = -2

=> y = -2/-2

=> y = 1

substitute in (1)

x + 3 = 2

=> x = 2 - 3

=> x = -1

**We get x = -1 and y = 1**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now